2016
DOI: 10.2217/whe-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Bremelanotide for Female Sexual Dysfunctions in Premenopausal Women: A Randomized, Placebo-Controlled Dose-Finding Trial

Abstract: Aim: Evaluate efficacy/safety of bremelanotide (BMT), a melanocortin-receptor-4 agonist, to treat female sexual dysfunctions in premenopausal women. Methods: Patients randomized to receive placebo or BMT 0.75, 1.25 or 1.75 mg self-administered subcutaneously, as desired, over 12 weeks. Primary end point was change in satisfying sexual events/month. Secondary end points included total score changes on female sexual function index and female sexual distress scale-desire/arousal/orgasm. Results: Efficacy data, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 31 publications
(47 reference statements)
1
62
0
2
Order By: Relevance
“…This increase is comparable to or greater than recent clinical trials studying other treatments for women with desire and/or arousal subtypes of FSD. In the BEGONIA trial investigating FDA‐approved flibanserin for hypoactive sexual desire, the treatment group total FSFI score improved by 5.3 against the placebo group increase of 3.5 , while a study of bremelanotide saw a total FSFI increase of 4.4 in the most effective treatment group against a placebo increase of 1.9 . Clinical studies of neuromodulation, which presumably would benefit genital arousal disorders over hypoactive sexual desire, have reported a total FSFI score increase of 6.5 in a group of patients receiving PTNS for OAB and 4.3 in a group of patients with SNM implants , with other SNM and PTNS neuromodulation studies reporting even smaller FSFI increases (range: 2.1–3.3) .…”
Section: Discussionmentioning
confidence: 99%
“…This increase is comparable to or greater than recent clinical trials studying other treatments for women with desire and/or arousal subtypes of FSD. In the BEGONIA trial investigating FDA‐approved flibanserin for hypoactive sexual desire, the treatment group total FSFI score improved by 5.3 against the placebo group increase of 3.5 , while a study of bremelanotide saw a total FSFI increase of 4.4 in the most effective treatment group against a placebo increase of 1.9 . Clinical studies of neuromodulation, which presumably would benefit genital arousal disorders over hypoactive sexual desire, have reported a total FSFI score increase of 6.5 in a group of patients receiving PTNS for OAB and 4.3 in a group of patients with SNM implants , with other SNM and PTNS neuromodulation studies reporting even smaller FSFI increases (range: 2.1–3.3) .…”
Section: Discussionmentioning
confidence: 99%
“…Bremelanotide was taken into a phase 2 trial in postmenopausal women with self-reported sexual dysfunction [277]. A total of 327 women with female sexual arousal disorder and/or hypoactive sexual desire disorder were randomized in a double-blind placebo-controlled study.…”
Section: Clinical Candidatesmentioning
confidence: 99%
“…Efficacy was determined as changes in score using the self-reported female sexual distress scale-desire/arousal/orgasm via an electronic diary for all sexual encounters for the duration of the study. Results indicated a significant increase in the number of sexual encounters per month (+0.75 for the 1.25/1.75 mg pooled data) in addition to a decrease in the distressed scores produced from the self-reported questionnaire (indicating greater satisfaction) [277]. Positive results were also reported from a phase 3 clinical study in August 2016 in premenopausal women, and may perhaps be the first US approved melanocortin ligand drug.…”
Section: Clinical Candidatesmentioning
confidence: 99%
“…This drug, flibanserin, is taken daily to increase overall sexual desire. There are other therapies in late stages of clinical development [5][6][7][8] that are not taken daily, but instead taken on-demand, i.e. when a woman with HSDD/FSIAD wants to want to have sex.…”
Section: Introductionmentioning
confidence: 99%